Hadith #3540 - Sahih Muslim - Aiyub (Sahih Muslim)
Umar (Allah be pleased with him) asked Allah’s Apostle (ﷺ) about it and he commanded him that he should take her back until she is divorced in the state of purity without having a sexual intercourse with her, and said: Divorce her in the beginning of her ‘Idda or her ‘Idda commences.
Grade: Sahih

Hadith #4135 - Sahih Muslim - Aiyub (Sahih Muslim)
We were sitting in the company of Abu Musa that he called for food and it consisted of flesh of fowl. It was then that a person from Banu Tamim visited him. His complexion was red having the resemblance of a slave. He said to him: Come and (join me in food). He showed reluctance. He (Abu Masa) said: Come on, for I saw Allah’s Messenger (ﷺ) eating it (fowl’s meat), whereupon that person said: I saw it eating something (of filth and rubbish) and I found it repugnant and took an oath that I w
Grade: Sahih

Hadith #5961 - Sahih Muslim - Aiyub (Sahih Muslim)
The greatest sinner of the Muslims amongst Muslims is one who asked about a certain thing which had not been prohibited and it was prohibited because of his asking about it.
Grade: Sahih

Hadith #6703 - Sahih Muslim - Aiyub (Sahih Muslim)
Much wrong (Zulman Kathira).
Grade: Sahih